A new core–shell-type nanoparticle loaded with paclitaxel/norcantharidin and modified with APRPG enhances anti-tumor effects in hepatocellular carcinoma - Xie, Ming-Hua; Fu, Zai-Lin; Hua, Ai-Lian; Zhou, Ji-Fang; Chen, Qian; Li, Jian-Bo; Yao, Shen; Cai, Xin-Jun; Ge, Min; Zhou, Li; Wu, Jia (Frontiers in Oncology, 2022)
Nanoparticle delivery systems have been shown to improve the therapeutic efficacy of anti-cancer drugs, including a variety of drugs for the treatment of hepatocellular carcinoma (HCC). However, the current systems show some limitations and the delivery of more effective nanoparticle systems for anti-HCC drugs with better targeting ability are needed. Here, we created paclitaxel (PTX)/norcantharidin (NCTD)-loaded core-shell lipid nanoparticles modified with a tumor neovasculature-targeted peptide (Ala-Pro-Arg-Pro-Gly, APRPG) and investigated their anti-tumor effects in HCC. Core-shell type lipid nanoparticles (PTX/NCTD-APRPG-NPs) were established by combining poly (lactic-co-glycolic acid) (PLGA)-wrapped PTX with phospholipid-wrapped NCTD, followed by modification with APRPG. For comparison, PTX-loaded PLGA nanoparticles (PTX-NPs) and PTX/NCTD-loaded core-shell type nanoparticles without APRPG (PTX/NCTD-NPs) were prepared. The in vitro and in vivo anti-tumor effects were examined in HepG2 cells and tumor-bearing mice, respectively. Morphological and release characterization showed that PTX/NCTD-APRPG-NPs were prepared successfully and achieved up to 90% release of PTX in a sustained manner. Compared with PTX/NCTD-NPs, PTX/NCTD-APRPG-NPs significantly enhanced the uptake of PTX. Notably, the inhibition of proliferation and migration of hepatoma cells was significantly higher in the PTX/NCTD-APRPG-NP group than those in the PTX-NP and PTX/NCTD-NP groups, which reflected significantly greater anti-tumor properties as well. Furthermore, key molecules in cell proliferation and apoptosis signaling pathways were altered most in the PTX/NCTD-APRPG-NP group, compared with the PTX-NP and PTX/NCTD-NP groups. Collectively, PTX/NCTD-loaded core-shell lipid nanoparticles modified with APRPG enhance the effectiveness of anti-HCC drugs and may be an effective system for the delivery of anti-HCC drugs.